ANALYSIS OF THE LABOUR RESOURCES USAGE IN AGRICULTURAL ENTERPRISES OF UKRAINE: A CASE STUDY OF THE VOLYN REGION - Oleksandr SHUBALYI; Nadia RUD; Iryna SHUBALA; Antonina GORDIICHUK; Oksana KIIILUKHA; Natalia VASILIK (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The article examines the specifics of the use of labor resources in the agricultural sector of Ukraine. The problems associated with ensuring the proper level of efficiency in the use of labor resources at agricultural enterprises of Ukraine have been identified, the demographic aging of the rural population is particularly important. The state of use of labor resources at agricultural enterprises was analyzed using the example of the Volyn region. The dynamics of the specific weight of employees of agricultural enterprises and the dynamics of personnel turnover indicators were determined. An econometric model of the dependence of personnel wages on the efficiency of agricultural production has been developed. The problems of ensuring proper working conditions for the personnel of agricultural enterprises of the Volyn region and the dynamics of compensation payments were considered.